The IASLC Lung Cancer Staging Project: Proposals for Coding T Categories for Subsolid Nodules and Assessment of Tumor Size in Part‐Solid Tumors in the Forthcoming Eighth Edition of the TNM Classification of Lung Cancer. Issue 8 (August 2016) - Travis, William D.; Asamura, Hisao; Bankier, Alexander A.; Beasley, Mary Beth; Detterbeck, Frank; Flieder, Douglas B.; Goo, Jin Mo; MacMahon, Heber; Naidich, David; Nicholson, Andrew G.; Powell, Charles A.; Prokop, Mathias; et al.
Abstract : ABSTRACT : This article proposes codes for the primary tumor categories of adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) and a uniform way to measure tumor size in part‐solid tumors for the eighth edition of the tumor, node, and metastasis classification of lung cancer. In 2011, new entities of AIS, MIA, and lepidic predominant adenocarcinoma were defined, and they were later incorporated into the 2015 World Health Organization classification of lung cancer. To fit these entities into the T component of the staging system, the Tis category is proposed for AIS, with Tis (AIS) specified if it is to be distinguished from squamous cell carcinoma in situ (SCIS), which is to be designated Tis (SCIS). We also propose that MIA be classified as T1mi. Furthermore, the use of the invasive size for T descriptor size follows a recommendation made in three editions of the Union for International Cancer Control tumor, node, and metastasis supplement since 2003. For tumor size, the greatest dimension should be reported both clinically and pathologically. In nonmucinous lung adenocarcinomas, the computed tomography (CT) findings of ground glass versus solid opacities tend to correspond respectively to lepidic versus invasive patterns seen pathologically. However, this correlation is not absolute; so when CT features suggest nonmucinous AIS, MIA, and lepidic predominant adenocarcinoma, the suspected diagnosis and clinical staging should be regarded as a preliminary assessment that is subject to revision after pathologic evaluation of resected specimens. The ability to predict invasive versus noninvasive size on the basis of solid versus ground glass components is not applicable to mucinous AIS, MIA, or invasive mucinous adenocarcinomas because they generally show solid nodules or consolidation on CT.